Determinan Penentu Produktivitas Tenaga Kerja (Studi Kasus pada Pabrik Tahu di Kecamatan Sindangkasih) - Hadiyan, Edwin; Salsabila, Fauziyah Latiefa; Ranggajibja, Joelvian (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
The objective of this study is to determine and analyze the influence of salaries, technology, capital, and emotional intelligence on labor productivity at tofu factories in the Sindangkasih District. The research methodology used is descriptive with a quantitative approach. Data was collected directly from employees of the tofu factory in Sindangkasih District through a questionnaire, completed by 203 individuals. Simple random sampling was used to select the sample, and multiple linear regression was the analytical tool employed. The analysis of salaries, technology, capital, and emotional intelligence reveals that each of these factors significantly impacts labor productivity, both individually and collectively. Based on these findings, to further enhance labor productivity, it is crucial to increase salaries, improve technology to a more semi-modern level, increase rational capital, and consistently prioritize work as a form of worship, ensuring that work activities are seen as virtuous deeds.